Self-medications practice of patients visiting dermatology outpatient department of Chitwan Medical College - Parajuli, N; Jha, H K; Pokhrel, A (Journal of Chitwan Medical College, 2017)
A simple pretested questionnaire was used to find out on the pattern of self-medications and prior outside consultation in patient visiting Chitwan Medical College (CMC). A total of 160 patients were included in the study. Out of the total 160 respondents, 83.1% did some form of consultation outside medical college. Majority of them sought treatment from non-doctors (77.4%) to only a few (22.6%) with a medical doctor. Majority of the patients (88.1%) had some form of self-medications over the last one year period.